Predictors of Ischemic Stroke Among the Patients with end-Stage Renal Disease: A Single Centric Study of Local Population - Muhammad Usman, Yasir Hussain, Sajad Ahmad, Muhammad Wasif Baig, Talha Munir (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The incidence of stroke is greater in patients with end-stage renal disease (ESRD) as compared to the general population. It is thought that there may be a few extra risk factors in ESRD patients suffering from stroke as compared to ESRD patients without stroke. This study aims to better understand the risk factors for stroke that are unique to patients with ESRD. Methods: In order to find out the different causative factors influencing the production of ischemic stroke (IS) in patients with ESRD, we carried out this retrospective study at the DHQ hospital in Faisalabad. In this study total of sixty patients were recruited and further divided into two groups. The first group consisted of 30 patients with ESRD with a history of ischemic stroke, while 30 patients with stroke-free dialysis were selected as the age and gender control group. Patients with and without ischemic stroke were compared in terms of demographic characteristics, stroke risk factors, and lab results. Results: Patients with acute ischemic stroke had an average age of 56.70 ± 8.87 years with 52% male whereas the non-ischemic stroke group had an average age of 58.9 ± 9.20 years. Small vascular obstruction was found to be the most common subtype of IS (42%), followed by atherosclerosis of large vessels (28%). Compared with patients who did not have a stroke, patients who had a stroke had significantly higher rates of hypertension (HTN), higher systolic (SBP) and diastolic blood pressure (DBP) at admission. The group with a stroke had significantly lower total cholesterol and LDL cholesterol. Lower levels of low-density lipoprotein (LDL) and higher systolic blood pressure were found to be the independent risk factor for an ischemic stroke in a multivariate analysis (OR=1.025, 95% CI p=0.045 and OR=1.458, 95% CI, P=0.03 respectively). Conclusion: According to the findings of our study, ESRD patients with hypertension and diabetes have a higher chance of ischemic stroke and the lower LDL levels and higher systolic blood pressure were the independent predictors of ischemic stroke. Keywords: Hemodialysis, Ischemic stroke, risk factors, Hypertension, end stage renal disease,